2012
DOI: 10.1111/j.1835-2561.2012.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Client Importance and Auditor Independence: The Effect of the Asian Financial Crisis

Abstract: This paper investigates the effect of the Asian financial crisis on the relationship between client economic importance and auditor independence. Using data from 1994 to 2001 in six Asian markets (Hong Kong, Indonesia, Malaysia, Singapore, Taiwan and Thailand), we find that auditors are less likely to compromise their independence for important clients after a crisis. The result is consistent with Coffee's (2001) crash‐then‐law hypothesis and supports the notion that financial crisis triggers public concern ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…They could not, however, observe whether the importance of the client creates a close economic relationship between the audit client and the auditor. Zhou and Zhu (), who analysed the relationship between the economic importance of clients and auditor independence in Asian countries, assert that strict application of regulations after the Asian financial crisis reduced the possibility of compromising auditor independence. Lim and Tan () analysed the relationship between the NAS fee and the absolute values of discretionary accruals when industry experts participate.…”
Section: Prior Research and Nas Regulationsmentioning
confidence: 99%
“…They could not, however, observe whether the importance of the client creates a close economic relationship between the audit client and the auditor. Zhou and Zhu (), who analysed the relationship between the economic importance of clients and auditor independence in Asian countries, assert that strict application of regulations after the Asian financial crisis reduced the possibility of compromising auditor independence. Lim and Tan () analysed the relationship between the NAS fee and the absolute values of discretionary accruals when industry experts participate.…”
Section: Prior Research and Nas Regulationsmentioning
confidence: 99%
“…Li based on a change in the financial distress company inspected before and after the implementation of SOX; The study found that before the implementation of SOX, there is no significant correlation between client importance and auditors of financial distress probability Company issued a going concern audit opinion, but after the implementation of the bill, there was a significant positive correlation between the two [8] . Zhou and Zhu concerned about the impact of the Asian financial crisis which the importance of client relations and decision-making audit reports; They listed companies in six Asian countries for the study, before the Asian financial crisis, the probability of the importance of former clients and auditors issued a qualified audit opinions found irrelevant, and after the Asian financial crisis, as countries have strengthened investor protection system, this becomes a significant positive correlation between the two [9] . Based on data from China's ,Chen, Sun, and Wu [10] and Lu Zhengfei, [2] respectively in yinguangxia event and 2007 new accounting principles, auditing standards and the strengthening of law firm civil litigation risks as a cut-off point of China's macro-institutional environment, has also been a similar conclusion.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…The reason why this is the case, the relationship between client important and auditor reporting decision may be doesn't exist in isolation, but is influenced by a variety of external factors. Thus, researchers have begun to focus on macro-factors 1 that may affect the relationship between them [8][9][10] . However, changes in macroeconomic factors generally need to go through a lengthy process, but it is often not controllable for the CPA profession itself.…”
Section: Introductionmentioning
confidence: 99%
“…; Srivastava et al. ; Zhou and Zhu ). Our results suggest that the auditor designation rule, in fact, protects auditor independence, in the sense that designated auditors effectively evaluate firms’ listing possibilities and improve not only independence‐in‐appearance but independence‐in‐fact.…”
mentioning
confidence: 99%
“…First, this study could address how auditor practices are differently affected according to IPO eligibility. Prior studies discussing auditor behaviours have generally focused on the impact of auditing on problematic firms (Zhou and Zhu ; Lee et al. ).…”
mentioning
confidence: 99%